Risk Based Efficiency Study for Chinese Commercial Banks in Global Financial Crisis, A stochastic function approach - CANG, PINGYUAN (2012)
Abstract: The contagion of global financial crisis shocks the world’s banking industry. China as the world’s second largest economy and famous emerging market has improving but comparatively immature banking system. The crisis could enlarge risk exposure to the banking industry. Whether the global financial crisis affects the efficiency of Chinese commercial banks is one of the objectives of this study.